Akadеmik litsеylar o‗quv jarayonida mobil tеxnologiyalaridan foydadanishning ba‘zi masalalari - Tursunov, S.Q; Kadirov, U.E (SCIENCE and SOCIETY, 2023)
In the article, the author revealed some issues of achieving efficiency using mobile technologies in the educational process of academic lyceums.
Keywords: digital technology; digital educational technology; mobile technology; media; efficiency; block construction; mobile application